2016
DOI: 10.1002/art.39749
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging–Detected Features of Inflammation and Erosions in Symptom‐Free Persons From the General Population

Abstract: MRI-detected inflammation and erosions are prevalent in symptom-free persons from the general population, especially at older ages and at preferential locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
64
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 18 publications
11
64
1
1
Order By: Relevance
“…Thus, the limited sample size did not allow for a more precise investigation and analysis. Close association of MRI bone edema and bone erosion has been proved since these two bone changes often co-localize into the same bone [16,38]. In the present study, radiographic progression was found in only five patients from 24 subjects.…”
Section: Discussioncontrasting
confidence: 64%
“…Thus, the limited sample size did not allow for a more precise investigation and analysis. Close association of MRI bone edema and bone erosion has been proved since these two bone changes often co-localize into the same bone [16,38]. In the present study, radiographic progression was found in only five patients from 24 subjects.…”
Section: Discussioncontrasting
confidence: 64%
“…MRI does, however, provide an objective measure of inflammatory joint disease, a key and defining feature of RA. While very low levels of synovitis or osteitis may be common and non-specific,20 our use of validated cut-off scores that identify an informative degree of inflammatory disease is an advance over previous literature. Residual confounding by unmeasured factors is also possible in this observational study, although adjustment for baseline demographics, race, CCP antibody positivity and baseline disease activity did not substantially impact the results.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known since more than a decade that >10% of the joints of healthy individuals are PD-positive; it has recently been shown that 88% of 207 healthy subjects presented at least one joint with US abnormal findings: signs of SE in 52% of them, presence of SH in 48% (with or without PD positivity); in 64 subjects, SH was associated with SE and in eight cases with PD 16. Erosions can also be found in healthy subjects,16 a finding that has been recently corroborated by MRI 17. Given the fact that single US abnormalities may not represent pathological findings, it is the combination of different pieces of information such as the age of the patient, the grade of detected abnormality and the number of joints affected that may be more useful in the interpretation of the significance of US appearances.…”
mentioning
confidence: 86%